OPTIMALISASI PEMBIAYAAN BERBASIS BAGI HASIL PADA BANK DEVISA SYARIAH DI INDONESIA - Hermawan Riyanto (Jurnal Ekonomi dan Bisnis, 2016)
Islamic banking is a financial institution that uses the sharing system has a wide range ofproducts offered, especially in the task of channeling bank funds for financing one of which isprofit and loss sharing financing (Mudaraba and Musharaka). Suposed profit and loss sharingfinancing that dominates among other types of financing due in accordance with conventionalbanks as well differentiator, but the reality is not profit and loss sharing financing dominate. Thisstudy aims analyze the factors that affect profit and loss sharing financing. The purpose of thisstudy was to analyze the influence of deposits mudaraba, equivalent of profit sharing, spreadprofit sharing, and Non Performing Financing of profit and loss sharing financing. The populationwas islamic Banking in Indonesia, which consists of 11 banks. The samples used are selectedusing purposive sampling technique and only 4 bank in accordance with the criteria. The datais taken from the Quarterly Financing Reports Sharia Bank Devisa in Bank Indonesia’s websiteduring the period of 4 years from 2010 to 2013, in this study consisted of 64 observation points.The data collected were analyzed using descriptive statistics and multiple regression analysis.The result showed that the coefficient of determination through the four test variables: depositsmudaraba, equivalent of profit sharing, spread profit sharing, and Non Performing Financingcan explian the variation in the dependent variable for profit and loss sharing financing by70.4% while the rest is explained by other causes beyond the research variables. Four variablessimultaneously affect the results because the financing for the significance level of less than0.05. From the partial results variable equivalent of profit sharing has not significant affect toprofit and loss sharing financing and variable non-performing ratio has negative significant affectto profit and loss sharing financing, while the other two variables deposits mudaraba and spreadprofit sharing has positive significant affect to profit and loss sharing financing.Keywords : deposits mudaraba, equivalent of profit sharing, spread profit sharing, and NonPerforming Financing of profit and loss sharing financing.